Pharmacokinetics and Pharmacodynamics of an Oral Formulation of Apixaban in Horses After Oral and Intravenous Administration - Serpa, Priscila B. S.; Brooks, Marjory B.; Divers, Thomas; Ness, Sally; Birschmann, Ingvild; Papich, Mark G.; Stokol, Tracy (Frontiers in Veterinary Science, 2018)
Horses with inflammatory and infectious disorders are often treated with injectable heparin anticoagulants to prevent thrombotic complications. In humans, a new class of direct oral acting anticoagulants (DOAC) appear as effective as heparin, while eliminating the need for daily injections. Our study in horses evaluated apixaban, a newly approved DOAC for human thromboprophylaxis targeting activated factor X (Xa). Our goals were to: (1) Determine pharmacokinetics and pharmacodynamics of apixaban after oral (PO) and intravenous (IV) administration in horses; (2) Detect any inhibitory effects of apixaban on ex vivo Equid herpesvirus type 1 (EHV-1)-induced platelet activation, and (3) Compare an anti-Xa bioactivity assay with ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) for measuring apixaban concentrations. In a blinded placebo-controlled cross-over study, five horses received a single dose (0.2 mg/kg) of apixaban or placebo PO or IV. Blood was collected before and at 3 (IV) or 15 (PO) min, 30 and 45 min, and 1, 2, 3, 4, 6, 8, and 24 h after dosing for measuring apixaban UPLC-MS concentrations and anti-Xa activity. Pharmacodynamic response was measured in a dilute prothrombin time (dPT) assay. Flow cytometric EHV-1-induced platelet P-selectin expression and clinical pathologic safety testing were performed at baseline, 2 and 24 h and baseline and 24 h, respectively. We found no detectable apixaban in plasma PO administration. After IV administration, plasma apixaban levels followed a two-compartment model, with concentrations peaking at 3 min and decreasing to undetectable levels by 8 h. The elimination half-life was 1.3 ± 0.2 h, with high protein binding (92–99%). The dPT showed no relationship to apixaban UPLC-MS concentration and apixaban did not inhibit EHV-1-induced platelet activation after IV dosing. Apixaban anti-Xa activity showed excellent correlation to UPLC-MS (r2 = 0.9997). Our results demonstrate that apixaban has no apparent clinical utility as an anticoagulant for horses due to poor oral availability.